Pelaksanaan Program “Madrasah Lancar Baca Al-Qur’an” di MTSN 3 Kota Pariaman - Putri Zahara Mudasir; Puti Andam Dewi; Eli Fitri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research was motivated by the school's concern about students' ability to read the Al-Qur'an at MTsN 3 Kota Pariaman which was still not fluent, this was known from the tahfiz program which was carried out every morning. Some students who are tahfiz leaders at the front are not fluent in reading the Koran and do not understand the correct rules of tajwid, especially new students. This makes it difficult for students to memorize and study the Al-Qur'an, where one of the subjects at this school is tahfiz lessons. This raises concerns from the school. One of the solutions designed by the school to overcome this problem is to implement "madrasah read the Koran fluently" program, this program was designed by the school as the school's responsibility as an educational institution that places great importance on the religious values of its students. The research aims to describe and illustrate to writers and readers the implementation of the "Madrasah fluent reading Al-Qur'an" program at MTsN 3 Kota Pariaman" and the results of this program. This research uses descriptive qualitative research. This research aims to provide a detailed description of the implementation of the "madrasah reading the Qur'an fluently" program. The focus is on describing the existing situation or circumstances without manipulation or change. Through this research the author obtained information from observations carried out directly in class VII and collected data on students who were fluent, less fluent and not fluent in that class, the author also conducted interviews with several informants regarding the implementation of the "madrasah fluent reading of the Qur'an" program. an". The results of this research are that the implementation of this program is quite effective in students' fluency in reading the Qur'an. This can be seen from 1) students can apply the rules of good Qur'an reading according to the laws of recitation, 2) Students are fluent in reading the Al-Qur'an and are confident to appear in the tahfiz implementation every morning in the field. 3) students are motivated to improve their ability to read the Koran. 4) strengthening religious values regarding the privileges of studying the Qoran.